Determinan Risk Taking Bank Perkreditan Rakyat Di Daerah Istimewa Yogyakarta - Rinofah, Risal (Universitas PGRI Yogyakarta, 2018)
The purpose of this research is to test the efficiency, diversification and ownership concentration on risk level of BPR banks in DIY. BPR is chosen because it has a closed relationship with SMEs due to its main functions on the micro economy growth through credit channeling.Research data on 26 BPR during 2012-2016 were tested using multiple regression analysis technique. The test concludes only the efficiency proven to affect the risk of BPR banks. While the level of income diversification and ownership concentration has no effect.Keywords: efficiency, diversification and concentration of ownership to the level risk